Dizziness and balance outcomes after two different postoperative rehabilitation approaches following neck surgery: analyses of a multicenter randomized controlled trial. (3rd April 2023) - Hermansen, Anna; Kammerlind, Ann-Sofi; Wibault, Johanna; Löfgren, Håkan; Zsigmond, Peter; Dedering, Åsa; Öberg, Birgitta; Peolsson, Anneli
ABSTRACT: Background: Dizziness and balance problems are common symptoms in patients with cervical radiculopathy. Objective: To evaluate the effect of neck surgery postoperatively combined with either structured rehabilitation or standard approach in patients with cervical radiculopathy and dizziness and/or balance problems, and investigate factors influencing dizziness and balance at 6-month follow-up. Methods: Individuals (n = 149) with cervical radiculopathy and dizziness and/or balance problems were randomized preoperatively to structured postoperative rehabilitation or standard postoperative approach. Outcomes were intensity of dizziness and subjective balance, and clinical measures of balance. Results: Self-reported measures improved at three months (p ˂ 0.001 to p = .007) and the standing balance at six months (p = .008). No between-group differences. Baseline values, neck pain, and physical activity level explained 23–39% of the variance in 6-month outcomes for self-reported measures. Baseline values and physical activity level explained 71% of the variance in walking balance, and lower baseline scores were significantly associated with standing balance impairments (OR 0.876). Conclusion: Patients improved significantly in dizziness and subjective balance intensity shortly after surgery, and in standing balance at 6 months, independent of postoperative rehabilitation. Neck pain, physical activity, and neck muscle function influenced dizziness and balance, although preoperative values and neck pain were of most importance for 6-month outcomes.